Study of the utility of blood culture in febrile children aged between 3 months to 12 years admitted in a tertiary centre - ., Zosangliani; Thele, Rukuwe; Sharma, Manisha; S., Niranjana; Kambiakdik, T. (International Journal of Contemporary Pediatrics, 2020)
Background: Fever, the most common complaint that led patients to seek healthcare, indicates an underlying infection which could either be simple self-limiting viral infections or life threatening bacterial infections. It’s greatest challenge is the risk of occult bacteraemia, for which blood culture is the gold standard for the diagnosis. Objectives was to determine the proportion of blood culture positives among febrile children and to describe the bacteriological profile and antibiogram of blood culture isolates. Methods: A cross sectional study was done in the Department of Paediatrics and Microbiology, RIMS Hospital, Imphal. After obtaining consent (verbal assent in >7 years), blood culture samples were drawn from 200 children aged between 3 months to 12 years. The data was analysed using descriptive statistics. Chi square test was used and p-value of less than 0.05 taken as statistically significant. Results: Culture positivity was seen in 17 cases (8.5%) of which, participants who were less than 1 year of age and without proper immunisation record showed the highest positivity rate. It was higher in fever with localizing signs (9.2%) than those with fever without focus (7.8%). Gram positives constituted 11 (64.7%) of the isolates while 35.3% were Gram negatives. Staphylococcus aureus was the only Gram positive isolate. Of them, 4 were MRSA but all the strains were sensitive to Vancomycin and Linezolid. The most common Gram negative isolate was Acinetobacter spp and 80% of them were sensitive to Aminoglycosides while most of the Gram negatives were resistant to Ampicillin and 3rd generation Cephalosporins. All Acinetobacter spp were sensitive to Carbapenems but the only Pseudomonas spp isolated was sensitive only to Colistin. Conclusions: Blood culture positivity rate is relatively low in this study. However, studies with larger sample sizes are recommended to validate the findings. We emphasise the need for antibiotic stewardship